Identification of pharmacokinetic markers for safflower injection using a combination of system pharmacology, multicomponent pharmacokinetics, and quantitative proteomics study - Shi, Peiying; Ruan, Yijun; Zhong, Chenhui; Teng, Linglin; Ke, Liyuan; Yao, Hong (Frontiers in Pharmacology, 2022)
Safflower injection (SI), a water-extract preparation from safflower (Carthamus tinctorius L.), has been widely used for the treatment of cardio-cerebrovascular diseases. This work aims to develop an approach for identifying PK markers of cardiovascular herbal medicines using SI as a case study. Firstly, qualitative and quantitative analyses were performed to reveal ingredients of the preparation via HPLC-MS. Subsequently, multiple PK ingredients and integrated PK investigations were carried out to ascertain ingredients with favorable PK properties (e.g. easily detected at conventional PK time points and high system exposure) for the whole preparation. Next, ingredients against cardiovascular diseases (CVDs) in the preparation were predicted with target fishing and system pharmacology studies. Finally, ingredients with favorable PK properties, satisfactory PK representativeness for the preparation, and high relevance to CVDs were considered as potential PK markers. Their therapeutic effect was further evaluated using the H2O2-induced H9c2 cardiomyocyte-injured model and a proteomics study to identify objective PK markers. As results, it disclosed that SI mainly contains 11 ingredients. Among them, five ingredients, namely, hydroxysafflor yellow A (HSYA), syringin (SYR), p-coumaric acid (p-CA), scutellarin (SCU), and p-hydroxybenzaldehyde (p-HBA), showed favorable PK properties. HSYA, SYR, and rutin (RU) were predicted to show high relevance to CVDs and screened as potential PK markers. However, only HSYA and SYR were confirmed as therapeutic ingredients against CVDs. Combined with these findings, only HSYA demonstrated satisfactory representativeness on PK properties and therapeutic effects of multiple ingredients of the preparation, thereby indicating that HSYA is a potential PK marker for the SI. The results of this study can provide a reference for the characterization of PK markers for traditional Chinese medicines.